Perineal colostomy: advantages and disadvantages - Francesk Mulita; Konstantinos Tepetes; Georgios-Ioannis Verras; Elias Liolis; Levan Tchabashvili; Charalampos Kaplanis; Ioannis Perdikaris; Dimitrios Velissaris; Ioannis Maroulis (Gastroenterology Review)
The perineal colostomy is a reconstruction method performed after abdominoperineal resection for rectal malignancy. In this technique, the permanent colostomy is not placed in the left quadrant of the abdomen, but in the perineum. According to the literature, this technique provides many advantages such as a higher degree of satisfaction and greater quality of life to patients. Although this method could be a good option in selected patients, physicians should always be aware of the disadvantages of perineal colostomy.